A Study of Clinical Image Segmentation Using Deep Learning Methods - Dr. Anshu Srivastava; Abhishek Chandra; Abid Mohsan Zaidi; Akshay Kr. Sonker; Shashank Dwivedi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Rapidly, deep learning approaches have emerged as the go-to approach for assessing medical picture segmentation. The basic ideas of this study is to apply on picture segmentation , along with an analysis of various contributions made to the deep learning medical field, covering  main common problems that have been published recently. In remote sensing applications such as precision agriculture and urban planning, deep learning-based image segmentation has proven effective in segmenting satellite images. Additionally, Deep Learning algorithm has been used to segment photos taken by drones (UAVs), giving a chance to solve the environmental issues associated with warming. Deep learning research can be used a different type of tasks, like as object detection, image’s classification, segmentation, and registration. First, an overview of deep learning frameworks, applications, and methodologies is given. The best uses for deep learning techniques are briefly described. According to this study, there has been prior experience with several methods in the medical image segmentation class limited classification accuracy, limited segmentation resolution, and poor picture enhancement are just a few of the issues in medical image analysis that deep learning has been developed to address. In order to address these current problems and enhance the development of medical image segmentation challenges, we offer recommendations for further study.
Keywords: Deep Learning; Image Classification; Segmentation; Medical Image